Maternal mortality in a tertiary care hospital: a five-year review - Kaur, Manjeet; Mohi, Manjit K.; Aggarwal, Sangeeta; Kaur, Balwinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was aimed at analyzing the maternal mortality ratio over five years, the causes leading to maternal deaths in a tertiary care hospital and factors which are preventable. Methods: The records of maternal death from August 2010 to July 2015 (5 years) were collected and analyzed. Various factors like maternal age, parity, literacy, place of residence, antenatal registration, admission-death interval, mode of delivery and causes of deaths were reviewed. Results: The mean maternal mortality ratio (MMR) was 1039. The direct causes of maternal mortality were hemorrhage (22.4%), eclampsia (21.2%), sepsis (18.78%) and amniotic fluid embolism (8.48%). Indirect obstetric deaths were due to hepatitis (10.9%), anemia (3.6%), respiratory diseases (6.06%), heart diseases (3.03%), CNS disease (5.45%). Most of the deaths (69.7%) occurred in age group 20 and30 years. 63.6% were multigravida and 85.4% were unbooked cases. Conclusions: Antenatal care, screening and management of high risk pregnancies are most important to prevent complications and maternal deaths by timely detection and intervention.